Methotrexate Induced Neurotoxicity in Osteosarcoma: Case Report and Narrative Review of the Literature - Tsappa, Irene; Pilavaki, Pampina; Fotiou, Eleni; Constantinidou, Anastasia (Archives of Clinical and Biomedical Research, 2023)
Methotrexate (MTX) is a cytotoxic antimetabolite, which interferes with folic acid metabolism. The term high dose Methotrexate (HDMTX) refers to doses over 500 mg /m2 which are currently used to treat not only hematological malignancies but also solid neoplasms. Patients receiving intravenous (IV) HDMTX as part of their regime often experience a variety of side effects such as oral and gastrointestinal mucositis, nephrotoxicity and bone marrow suppression. Approximately 11% of these patients develop neurological symptoms and signs suggestive of MTX induced neurotoxicity, a condition, which is further, classified as acute, subacute and chronic depending on the time of onset. In this report we present a 22-year-old female with a high grade chondroblastic osteosarcoma of the pelvis who developed an isolated central facial nerve palsy acutely after the administration of IV HDMTX. Furthermore, we conducted a narrative review using Pubmed and included all patients with osteosarcoma who developed a transient or a permanent neurologic deficit during their treatment with IV HDMTX. Most patients presented with symptoms involving higher cognitive function, seizures and stroke like symptoms. To our knowledge this is the first case with isolated central facial nerve palsy acutely after the administration of IV HDMTX.